Exploring Pedagogical Practices at Al-Mujadid Islamic Boarding School: An In-depth Analysis of Learning Activities and Educational Strategies - Agustriani, Ely (Lembaga KITA, 2023)
The learning process in Islamic boarding schools (Pondok Pesantren) holds unique characteristics compared to conventional education systems. Operating within a traditional framework that allows for substantial autonomy, these institutions foster a reciprocal relationship between religious scholars (ulama) and students (santri). However, in contemporary times, a trend of modernized, integrated pesantren has emerged, blending elements from both traditional and modern educational systems. This thesis delves into the teaching and learning processes at Al-Mujaddid Islamic Boarding School in Sabang City, aiming to explore the instructional activities, curriculum, methods, facilities, and teaching patterns. The research methodology employs a descriptive approach, incorporating both literature review and field research methods such as observation, interviews, and surveys. The study involves a sample of 50 students, 18 teachers, and one administrative leader from Al-Mujaddid Islamic Boarding School. The findings indicate that the learning activities at Al-Mujaddid are well-organized, disciplined, and efficient, allowing students to focus on their studies and activities. The teaching methods employed include lectures, discussions, question-and-answer sessions, experiments, demonstrations, and dramatizations. While the facilities at Al-Mujaddid are generally comprehensive, the absence of a piped water supply (PAM) is noted. In terms of the teaching system and approach, Al-Mujaddid Islamic Boarding School adopts the Modern Gontor teaching method. This method features an integrative curriculum, combining religious and general knowledge into a cohesive unit. It is also comprehensive, addressing intellectual, emotional, and spiritual development across cognitive, affective, and psychomotor domains. The research concludes by urging local authorities (Pemda) to prioritize the necessary facilities for Al-Mujaddid Islamic Boarding School. Additionally, parents are encouraged to consider enrolling their children in the institution, fostering a supportive environment for both students and teachers.